A comparison of school effectiveness factors for socially advantaged and disadvantaged students in ten European countries in TIMSS 2011 - Sandoval-Hernández, Andrés (Šolsko polje, 2014)
Over the last decades, Educational Effectiveness Research (EER) has made considerable progress in terms of identifying school characteristics consistently associated with academic achievement. However, the critics of this body of research argue that while purporting to be inclusive and comprehensive, EER theoretical models often ignore the needs of children from disadvantaged backgrounds. The argument underlying this criticism is that students from socially disadvantaged families live and study in different contexts, and therefore have different educational needs than their more socially advantaged peers. In order to contribute to the debate on this topic, in this paper we empirically test recently developed EER theoretical model with two samples, one of disadvantaged and one of non-disadvantaged students. By using HLM analyses, we evaluate the fit of our selected EER theoretical model in the two samples, and compare the results across ten European countries. The data stems from the Trends in International Mathematics and Science Study (TIMSS) 2011 conducted by the). Our results suggest that, in general, the analyzed EER model fit the data of the non-disadvantaged students in most countries better. The implications of this finding for research and policy are discussed in the final section of the paper.
Keywords: vzgoja in izobraževanje; učni dosežki; education; educational effectiveness; učenci; disadvantages students; preverjanje znanja; TIMSS; mednarodne raziskave; matematika; mathematics; naravoslovje